Positive electrode active material, lithium ion secondary battery, and method for producing positive electrode active material

By reducing surface halogen content in the positive electrode active material through ion exchange and milling, the material achieves high capacity during high-speed charging and discharging, addressing the limitations of conventional O2 type structures.

JP7616039B2Active Publication Date: 2025-01-17TOYOTA JIDOSHA KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021205153
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-17
Publication Date
2025-01-17
Estimated Expiration
2041-12-17

AI Technical Summary

Technical Problem

Conventional positive electrode active materials with an O2 type structure have limited capacity during high-speed charging and discharging due to the presence of halogen-containing phases that inhibit lithium ion diffusion.

Method used

A positive electrode active material with a specific composition (Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O 2) is produced by reducing the surface halogen content through ion exchange with lithium halide and subsequent mechanical milling or pickling, ensuring a peak intensity ratio of halogen to oxygen of less than 1/1000 as measured by X-ray photoelectron spectroscopy (XPS).

Benefits of technology

The solution enables high capacity during high-speed charging and discharging, with the lithium ion secondary battery maintaining at least 60% of its capacity at 5C compared to 0.1C, while conventional materials suffer significant capacity loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616039000004
    Figure 0007616039000004
  • Figure 0007616039000005
    Figure 0007616039000005
  • Figure 0007616039000006
    Figure 0007616039000006
Patent Text Reader

Abstract

To disclose a cathode active material having a O2 type structure that has a high capacity at a high speed discharge.SOLUTION: A cathode active material having a O2 type structure is the cathode active material that a ratio I1 / I2 of a peak intensity I1 derived from halogen and a peak intensity I2 derived from a 1s electron of oxygen becomes 1 / 1000 or less when a front surface of the cathode active material is analyzed by an X-ray photoelectron spectroscopy (XPS).SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application discloses a positive electrode active material, a lithium ion secondary battery, and a method for producing the positive electrode active material. [Background technology]

[0002] A cathode active material having an O2 type structure is known. The cathode active material having an O2 type structure is stable even at high potential, so that charging and discharging in a high potential region can be utilized, and for example, high energy density can be easily obtained. The cathode active material having an O2 type structure is obtained by substituting at least a part of Na of a Na compound having a P2 type structure with Li. Specifically, as disclosed in Patent Documents 1 and 2, a cathode active material having an O2 type structure is obtained by performing ion exchange with a lithium halide on a Na compound having a P2 type structure and substituting at least a part of Na with Li. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2021-068556 [Patent Document 2] Patent Publication No. 2021-068555 Summary of the Invention [Problem to be solved by the invention]

[0004] Conventional positive electrode active materials with an O2 structure have room for improvement in terms of capacity during high-speed charge and discharge. [Means for solving the problem]

[0005] As one of the means for solving the above problems, the present application provides: A positive electrode active material having an O2 type structure, When the surface of the positive electrode active material is analyzed by X-ray photoelectron spectroscopy (XPS), the ratio I1 / I2 of the peak intensity I1 derived from a halogen to the peak intensity I2 derived from an oxygen 1s electron is 1 / 1000 or less. positive electrode active material Disclose.

[0006] The positive electrode active material of the present disclosure is Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O2 (wherein the relationships 0≦a≦1, 0≦b≦0.05, x+y+z=1, and 0≦p+q+r≦0.2 are satisfied, and M is at least one element selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W).

[0007] As one of the means for solving the above problems, the present application provides: A lithium ion secondary battery having a positive electrode, an electrolyte layer, and a negative electrode, The positive electrode comprises the positive electrode active material of the present disclosure; Lithium-ion secondary battery Disclose.

[0008] As one of the means for solving the above problems, the present application provides: A method for producing a positive electrode active material, comprising: Obtaining a Na compound having a P2 type structure; by ion exchange using lithium halide, at least a part of the Na in the Na compound is replaced with Li to obtain a Li compound having an O2 type structure; and Reducing the amount of halogen present per unit area on the surface of the Li compound; A manufacturing method comprising: Disclose.

[0009] In the manufacturing method of the present disclosure, the amount of halogen present per unit area on the surface of the Li compound may be reduced by at least one of pickling the surface of the Li compound and crushing primary particles of the Li compound by mechanical milling. Effect of the Invention

[0010] The positive electrode active material of the present disclosure is likely to ensure high capacity during high-rate charging and discharging. [Brief description of the drawings]

[0011] [Figure 1] 1 illustrates a schematic configuration of a lithium ion secondary battery. [Diagram 2] 1 shows X-ray diffraction peaks of positive electrode active materials according to examples and comparative examples. [Diagram 3] 1 shows XPS spectra of positive electrode active materials according to examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] 1.Cathode active material The positive electrode active material of the present disclosure has an O2 type structure. When the surface of the positive electrode active material of the present disclosure is analyzed by XPS, the ratio I1 / I2 of the peak intensity I1 derived from a halogen element to the peak intensity I2 derived from an oxygen 1s electron is 1 / 1000 or less.

[0013] 1.1 Crystal structure The positive electrode active material of the present disclosure includes at least an O2 type structure (belonging to space group P63mc) as a crystal structure. The positive electrode active material of the present disclosure has an O2 type structure and may have a crystal structure other than the O2 type structure. Examples of crystal structures other than the O2 type structure include a T♯2 type structure (belonging to space group Cmca) formed when Li is de-inserted from the O2 type structure and an O6 type structure (belonging to space group R-3m, with a c-axis length of 2.5 nm to 3.5 nm, typically 2.9 nm to 3.0 nm, and different from the O3 type structure also belonging to space group R-3m). The positive electrode active material of the present disclosure may have an O2 type structure as a main phase, or may have a crystal structure other than the O2 type structure as a main phase. The positive electrode active material of the present disclosure may have a crystal structure as a main phase that changes depending on its charge / discharge state.

[0014] 1.2 Composition The composition of the positive electrode active material of the present disclosure is not particularly limited as long as it has the above crystal structure. The positive electrode active material having an O2 type structure may, for example, contain at least one of Li and Na, a transition metal element, and O as constituent elements, or may contain at least Li, a transition metal element, and O. Examples of the transition metal element include at least one element of Mn, Ni, and Co. In particular, when the constituent elements include at least Li, Mn, at least one of Ni and Co, and O, the performance of the positive electrode active material of the present disclosure is likely to be further improved when the constituent elements include at least Li, Mn, Ni, Co, and O. However, the positive electrode active material of the present disclosure may, for example, be completely released by charging, and the presence of Li may become substantially zero.

[0015] The positive electrode active material of the present disclosure is Li a Na b Mn x-p Ni y-q Co z-r M p+q+rThe composition may be represented by O2, where the relationships 0≦a≦1, 0≦b≦0.05, x+y+z=1, and 0≦p+q+r≦0.2 are satisfied. M is at least one element selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W. When the composition is such, the O2 type structure is easily maintained.

[0016] In the above composition, a may be 0 or more, more than 0, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, or 0.6 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, or 0.7 or less. In the above composition, b may be 0.05 or less, 0.04 or less, 0.03 or less, 0.02 or less, 0.01 or less, or 0. In the above composition, x may be 0 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, or 0.5 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less. In the above composition, y may be 0 or more, 0.1 or more, or 0.2 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, or 0.2 or less. In the above composition, z may be 0 or more, 0.1 or more, 0.2 or more, or 0.3 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, or 0.3 or less. Many M do not contribute to charge and discharge. In this respect, by having p+q+r be 0.2 or less, a high charge and discharge capacity is easily ensured. p+q+r may be 0.1 or less, or may be 0. The composition of O is approximately 2, but is not necessarily exactly 2.0 and is indefinite.

[0017] In the above composition, when the valence of M is +n, the relationship 3.0≦4(xp)+2(yq)+3(zr)+n(p+q+r)≦3.5 may be satisfied. This is intended to be a range in which the total valence of metals in the positive electrode active material is close to 3.33 (charge neutral when a is 0.67). As described later, a positive electrode active material having an O2 type structure is synthesized via a Na compound having a P2 type structure, and the charge neutrality occurs when the Na composition at this time is in the range of 0.5 to 1.0, which corresponds to the case where the above relationship is satisfied. Here, the upper limit value 1.0 for the Na composition is the maximum composition in the structure. Also, if the Na composition is below the lower limit value 0.5, it becomes difficult to maintain the P2 type structure.

[0018] The composition of the positive electrode active material can be determined, for example, by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0019] 1.3 Presence of halogens on the surface A positive electrode active material having an O2 type structure is obtained by performing ion exchange with a lithium halide on a Na compound having a P2 type structure, and replacing at least a part of the Na in the Na compound with Li. In the positive electrode active material obtained in this way, a reaction phase containing a halogen is formed near the surface, and this reaction phase tends to inhibit the diffusion of lithium ions. As a result, lithium ions cannot be sufficiently inserted and removed during high-speed charging and discharging, and the capacity decreases.

[0020] In contrast, when the surface of the positive electrode active material of the present disclosure is analyzed by XPS, the ratio I1 / I2 of the peak intensity I1 derived from the halogen element to the peak intensity I2 derived from the 1s electron of oxygen is 1 / 1000 or less. In addition, when a protective layer described later exists on the surface of the positive electrode active material, when the surface is analyzed by XPS while removing at least twice the thickness of the protective layer by sputtering, the ratio I1 / I2 of the maximum value of the peak intensity I1 derived from the halogen to the peak intensity I2 derived from the 1s electron of oxygen at the same sputtering depth as the above is 1 / 1000 or less. The "peak derived from the halogen" may be appropriately selected according to the type of halogen. Specifically, it may be a peak derived from the 1s electron for F, a peak derived from the 2p or 2s electron for Cl, a peak derived from the 3d or 3p3 / 2 electron for Br, and a peak derived from the 3d5 / 2 or 3p3 / 2 for I. In the spectrum obtained by XPS, the position of the peak originating from the oxygen 1s electron and the position of the peak originating from the halogen are publicly known (for example, the peak originating from O1s appears near 530 eV, and the peak originating from Cl2p appears near 198 to 200 eV). Here, from the viewpoint of the measurement accuracy of XPS, the peak intensity that is 1 / 1000 or less of the peak intensity I2 originating from the oxygen 1s electron is substantially equal to 0. That is, when the surface of the positive electrode active material is analyzed by XPS, if the peak intensity originating from the halogen is 1 / 1000 or less of the peak intensity originating from the oxygen 1s electron, it can be determined that the halogen is substantially not present on the surface of the positive electrode active material. In other words, the positive electrode active material of the present disclosure does not substantially have a halogen-containing phase in which lithium ions diffuse slowly near its surface, or if it does, it is only a very small amount. Therefore, lithium ions can be sufficiently inserted and removed even during high-speed charging and discharging, and high capacity is easily ensured. In a lithium ion secondary battery having the positive electrode active material of the present disclosure, the charge / discharge capacity when high-rate charging / discharging is performed is unlikely to decrease significantly compared to the charge / discharge capacity when low-rate charging / discharging is performed; for example, the charge / discharge capacity when high-rate charging / discharging is performed at 5 C is likely to be 60% or more of the charge / discharge capacity when low-rate charging / discharging is performed at 0.1 C.

[0021] 1.4 Other matters The shape of the positive electrode active material of the present disclosure may be any shape that is common for a positive electrode active material of a battery. For example, the positive electrode active material of the present disclosure may be particulate. The particles of the positive electrode active material may be solid particles, hollow particles, or particles having voids. The particles of the positive electrode active material may be primary particles, or secondary particles formed by agglomeration of a plurality of primary particles. The average particle diameter (D50) of the positive electrode active material may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. The average particle diameter D50 in the present application is the particle diameter (median diameter) at an integrated value of 50% in a volume-based particle size distribution obtained by a laser diffraction / scattering method.

[0022] 2.Positive electrode The technology of the present disclosure also has an aspect of a positive electrode containing the above-mentioned positive electrode active material. That is, the positive electrode of the present disclosure includes a positive electrode active material having an O2 type structure, and when the surface of the positive electrode active material is analyzed by XPS, the ratio I1 / I2 of the peak intensity I1 derived from a halogen element to the peak intensity I2 derived from the 1s electron of oxygen is 1 / 1000 or less. As shown in FIG. 1, a positive electrode 10 according to one embodiment may include a positive electrode active material layer 11 and a positive electrode current collector 12, and in this case, the positive electrode active material layer 11 may contain a positive electrode active material having the above-mentioned O2 type structure.

[0023] 2.1 Cathode active material layer The positive electrode active material layer 11 contains at least the positive electrode active material having the O2 type structure as the positive electrode active material, and may further contain an electrolyte, a conductive assistant, a binder, and the like. Furthermore, the positive electrode active material layer 11 may contain various other additives. The content of each of the positive electrode active material, electrolyte, conductive assistant, binder, and the like in the positive electrode active material layer 11 may be appropriately determined according to the target battery performance. For example, the content of the positive electrode active material may be 40 mass% or more, 50 mass% or more, or 60 mass% or more, and may be 100 mass% or less, or 90 mass% or less, assuming that the entire positive electrode active material layer 11 (total solid content) is 100 mass%. The shape of the positive electrode active material layer 11 is not particularly limited, and may be, for example, a sheet-like positive electrode active material layer 11 having a substantially flat surface. The thickness of the positive electrode active material layer 11 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.

[0024] 2.1.1 Cathode active material The positive electrode active material layer 11 may contain only the positive electrode active material having the O2 type structure as the positive electrode active material. Alternatively, the positive electrode active material layer 11 may contain, in addition to the positive electrode active material having the O2 type structure, a different type of positive electrode active material (another positive electrode active material). From the viewpoint of further enhancing the effect of the technology of the present disclosure, the content of the other positive electrode active material in the positive electrode active material layer 11 may be small. For example, the content of the positive electrode active material having the O2 type structure may be 50 mass% or more, 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, 95 mass% or more, or 99 mass% or more, based on the total positive electrode active material contained in the positive electrode active material layer 11 being 100 mass%.

[0025] The surface of the positive electrode active material may be covered with a protective layer containing a lithium ion conductive oxide. That is, the positive electrode active material layer 11 may include a composite having the above-mentioned positive electrode active material and a protective layer provided on the surface thereof. This makes it easier to suppress the reaction between the positive electrode active material and a sulfide (for example, a sulfide solid electrolyte described later). Examples of lithium ion conductive oxides include Li3BO3, LiBO2, Li2CO3, LiAlO2, Li4SiO4, Li2SiO3, Li3PO4, Li2SO4, Li2TiO3, Li4Ti5O 12 , Li2Ti2O5, Li2ZrO3, LiNbO3, Li2MoO4, and Li2WO4. The coverage (area ratio) of the protective layer may be, for example, 70% or more, 80% or more, or 90% or more. The thickness of the protective layer may be, for example, 0.1 nm or more or 1 nm or more, and may be 100 nm or less, or 20 nm or less.

[0026] 2.1.2 Electrolytes The electrolyte that can be contained in the positive electrode active material layer 11 may be a solid electrolyte, a liquid electrolyte (electrolytic solution), or a combination thereof.

[0027] The solid electrolyte may be any known solid electrolyte for lithium ion secondary batteries. The solid electrolyte may be an inorganic solid electrolyte or an organic polymer electrolyte. In particular, inorganic solid electrolytes are excellent in ion conductivity and heat resistance. Examples of inorganic solid electrolytes include lithium lanthanum zirconate, LiPON, Li 1+X Al X Ge 2-XExamples of the oxide solid electrolyte include (PO4)3, Li-SiO-based glass, and Li-Al-SO-based glass; and sulfide solid electrolytes such as Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Si2S-P2S5, Li2S-P2S5-LiI-LiBr, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and Li2S-P2S5-GeS2. In particular, sulfide solid electrolytes, particularly sulfide solid electrolytes containing at least Li, S, and P as constituent elements, have high performance. The solid electrolyte may be amorphous or crystalline. The solid electrolyte may be, for example, particulate. Only one type of solid electrolyte may be used alone, or two or more types may be used in combination.

[0028] The electrolyte may contain, for example, lithium ions as carrier ions. The electrolyte may be an aqueous electrolyte or a non-aqueous electrolyte. The composition of the electrolyte may be the same as that of the electrolyte of a lithium ion secondary battery. For example, the electrolyte may be a carbonate-based solvent in which a lithium salt is dissolved at a predetermined concentration. Examples of the carbonate-based solvent include fluoroethylene carbonate (FEC), ethylene carbonate (EC), and dimethyl carbonate (DMC). Examples of the lithium salt include LiPF6.

[0029] 2.1.3 Conductive additives Examples of the conductive assistant that may be included in the positive electrode active material layer 11 include carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); and metal materials such as nickel, aluminum, and stainless steel. The conductive assistant may be, for example, particulate or fibrous, and the size is not particularly limited. Only one type of conductive assistant may be used alone, or two or more types may be used in combination.

[0030] 2.1.4 Binders Examples of binders that can be included in the positive electrode active material layer 11 include butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, acrylate butadiene rubber (ABR)-based binders, styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVdF)-based binders, polytetrafluoroethylene (PTFE)-based binders, polyimide (PI)-based binders, etc. Only one type of binder may be used alone, or two or more types may be used in combination.

[0031] 2.2 Positive electrode current collector As shown in FIG. 1, the positive electrode 10 may include a positive electrode collector 12 in contact with the positive electrode active material layer 11. The positive electrode collector 12 may be any of those commonly used as a positive electrode collector for a battery. The positive electrode collector 12 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, or the like. The positive electrode collector 12 may be made of a metal foil or a metal mesh. In particular, a metal foil is excellent in terms of ease of handling. The positive electrode collector 12 may be made of a plurality of foils. Examples of metals constituting the positive electrode collector 12 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, and the like. In particular, from the viewpoint of ensuring oxidation resistance, the positive electrode collector 12 may contain Al. The positive electrode collector 12 may have some kind of coating layer on its surface for the purpose of adjusting resistance, or the like. The positive electrode current collector 12 may be a metal foil or a substrate plated or vapor-deposited with the above metal. When the positive electrode current collector 12 is made of a plurality of metal foils, some layer may be present between the plurality of metal foils. The thickness of the positive electrode current collector 12 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.

[0032] 2.3 Other In addition to the above configuration, the positive electrode 10 may have a general configuration as a positive electrode of a secondary battery. For example, a tab or a terminal. The positive electrode 10 can be manufactured by a known method, except that a positive electrode active material having the above O2 type structure is used. For example, the positive electrode active material layer 11 can be easily formed by forming a positive electrode mixture containing the above various components in a dry or wet manner. The positive electrode active material layer 11 may be formed together with the positive electrode current collector 12, or may be formed separately from the positive electrode current collector 12.

[0033] 3. Lithium-ion secondary battery As shown in FIG. 1, a lithium ion secondary battery 100 according to an embodiment has a positive electrode 10, an electrolyte layer 20, and a negative electrode 30. Here, the positive electrode 10 contains the positive electrode active material of the present disclosure. As described above, the positive electrode active material of the present disclosure can sufficiently insert and remove lithium ions even during high-rate charging and discharging, and a high capacity is easily obtained. In this regard, the performance of the secondary battery 100 is easily improved by including the positive electrode active material of the present disclosure in the positive electrode of the lithium ion secondary battery 100. A specific configuration example of the positive electrode 10 is as described above.

[0034] 3.1 Electrolyte layer The electrolyte layer 20 contains at least an electrolyte. When the lithium ion secondary battery 100 is a solid-state battery (a battery containing a solid electrolyte, which may be a battery partially using a liquid electrolyte in combination, or an all-solid-state battery not containing a liquid electrolyte), the electrolyte layer 20 contains a solid electrolyte and may further contain a binder or the like. In this case, the content of the solid electrolyte and the binder or the like in the electrolyte layer 20 is not particularly limited. On the other hand, when the lithium ion secondary battery 100 is an electrolyte battery, the electrolyte layer 20 contains an electrolyte solution and may further have a separator or the like for holding the electrolyte solution and preventing contact between the positive electrode active material layer 11 and the negative electrode active material layer 31. The thickness of the electrolyte layer 20 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.

[0035] The electrolyte contained in the electrolyte layer 20 may be appropriately selected from those exemplified as electrolytes that may be contained in the positive electrode active material layer described above. The binder that may be contained in the electrolyte layer 20 may also be appropriately selected from those exemplified as binders that may be contained in the positive electrode active material layer described above. The electrolyte and the binder may each be used alone or in combination of two or more. The separator may be any separator that is normally used in lithium ion secondary batteries, and examples of the separator include those made of resins such as polyethylene (PE), polypropylene (PP), polyester, and polyamide. The separator may have a single layer structure or a multi-layer structure. Examples of the multi-layer separator include a separator with a two-layer structure of PE / PP, or a separator with a three-layer structure of PP / PE / PP or PE / PP / PE. The separator may be made of a nonwoven fabric such as a cellulose nonwoven fabric, a resin nonwoven fabric, or a glass fiber nonwoven fabric.

[0036] 3.2 Negative electrode As shown in FIG. 1, the negative electrode 30 may include a negative electrode active material layer 31 and a negative electrode current collector 32.

[0037] 3.2.1 Negative electrode active material layer The negative electrode active material layer 31 includes at least a negative electrode active material, and may further include an electrolyte, a conductive assistant, a binder, and the like. Furthermore, the negative electrode active material layer 31 may further include various additives. The contents of the negative electrode active material, electrolyte, conductive assistant, binder, and the like in the negative electrode active material layer 31 may be appropriately determined according to the intended battery performance. For example, the content of the negative electrode active material may be 40 mass% or more, 50 mass% or more, or 60 mass% or more, and may be 100 mass% or less, or 90 mass% or less, with the entire negative electrode active material layer 31 (total solid content) being 100 mass%. The shape of the negative electrode active material layer 31 is not particularly limited, and may be, for example, a sheet-like negative electrode active material layer having a substantially flat surface. The thickness of the negative electrode active material layer 31 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.

[0038] As the negative electrode active material, various materials having a potential (charge / discharge potential) for absorbing and releasing lithium ions that is lower than that of the positive electrode active material having the above-mentioned O2 type structure can be used. For example, silicon-based active materials such as Si, Si alloys, and silicon oxide; carbon-based active materials such as graphite and hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium, lithium alloys, and the like can be used. Only one type of negative electrode active material may be used alone, or two or more types may be used in combination.

[0039] The shape of the negative electrode active material may be any shape that is common for a negative electrode active material of a battery. For example, the negative electrode active material may be in a particulate form. The negative electrode active material particles may be primary particles or secondary particles formed by agglomeration of a plurality of primary particles. The average particle diameter (D50) of the negative electrode active material particles may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. Alternatively, the negative electrode active material may be in a sheet form (foil form, film form) such as lithium foil. That is, the negative electrode active material layer 31 may be made of a sheet of the negative electrode active material.

[0040] Examples of the electrolyte that can be contained in the negative electrode active material layer 31 include the above-mentioned solid electrolyte, electrolytic solution, or a combination thereof. Examples of the conductive assistant that can be contained in the negative electrode active material layer 31 include the above-mentioned carbon material and metal material. The binder that can be contained in the negative electrode active material layer 31 may be appropriately selected from, for example, those exemplified as the binder that can be contained in the above-mentioned positive electrode active material layer 11. Only one type of electrolyte or binder may be used alone, or two or more types may be used in combination.

[0041] 3.2.2 Negative electrode current collector As shown in FIG. 1, the negative electrode 30 may include a negative electrode current collector 32 in contact with the negative electrode active material layer 31. The negative electrode current collector 32 may be any of those commonly used as a negative electrode current collector for a battery. The negative electrode current collector 32 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, or the like. The negative electrode current collector 32 may be a metal foil or a metal mesh, or may be a carbon sheet. In particular, a metal foil is excellent in terms of ease of handling. The negative electrode current collector 32 may be made of a plurality of foils or sheets. Examples of metals constituting the negative electrode current collector 32 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, and the like. In particular, from the viewpoint of ensuring reduction resistance and being difficult to alloy with lithium, the negative electrode current collector 32 may contain at least one metal selected from Cu, Ni, and stainless steel. The negative electrode current collector 32 may have some kind of coating layer on its surface for the purpose of adjusting the resistance or the like. The negative electrode current collector 32 may be a metal foil or a base material on which the above metal is plated or vapor-deposited. When the negative electrode current collector 32 is made of a plurality of metal foils, some kind of layer may be present between the plurality of metal foils. The thickness of the negative electrode current collector 32 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.

[0042] 3.3 Other matters The lithium ion secondary battery 100 may have the above-mentioned components housed inside an exterior body. Any known exterior body for a battery can be used as the exterior body. A plurality of batteries 100 may be electrically connected and stacked in any manner to form an assembled battery. In this case, the assembled battery may be housed inside a known battery case. The lithium ion secondary battery 100 may also have other obvious components such as necessary terminals. The shape of the lithium ion secondary battery 100 may be, for example, a coin type, a laminate type, a cylindrical type, a square type, or the like.

[0043] The lithium ion secondary battery 100 can be manufactured by applying a known method. For example, it can be manufactured as follows. However, the manufacturing method of the lithium ion secondary battery 100 is not limited to the following method, and each layer may be formed by, for example, dry molding or the like. (1) The negative electrode active material constituting the negative electrode active material layer is dispersed in a solvent to obtain a negative electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used, and N-methylpyrrolidone (NMP) can also be used. The negative electrode layer slurry is then applied to the surface of a negative electrode current collector using a doctor blade or the like, and then dried to form a negative electrode active material layer on the surface of the negative electrode current collector, forming a negative electrode. (2) The positive electrode active material constituting the positive electrode active material layer is dispersed in a solvent to obtain a positive electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used, and N-methylpyrrolidone (NMP) can also be used. The positive electrode layer slurry is applied to the surface of a positive electrode current collector using a doctor blade or the like, and then dried to form a positive electrode active material layer on the surface of the positive electrode current collector, which serves as a positive electrode. (3) The layers are laminated so that the electrolyte layer (solid electrolyte layer or separator) is sandwiched between the negative electrode and the positive electrode to obtain a laminate having the negative electrode current collector, the negative electrode active material layer, the electrolyte layer, the positive electrode active material layer, and the positive electrode current collector in this order. Other members such as terminals are attached to the laminate as necessary. (4) The laminate is housed in a battery case, and in the case of an electrolyte battery, the battery case is filled with electrolyte, and the laminate is immersed in the electrolyte and sealed in the battery case to form a secondary battery. In the case of an electrolyte battery, the electrolyte may be impregnated in the negative electrode active material layer, the separator, and the positive electrode active material layer at the above step (3).

[0044] 4. Manufacturing method of positive electrode active material The positive electrode active material of the present disclosure can be produced, for example, by the following method. That is, the method for producing the positive electrode active material of the present disclosure includes: Obtaining a Na compound having a P2 type structure; by ion exchange using lithium halide, at least a part of the Na in the Na compound is replaced with Li to obtain a Li compound having an O2 type structure; and Reducing the amount of halogen present per unit area on the surface of the Li compound; Includes.

[0045] 4.1 Synthesis of Na compounds with P2 structure Since the O2 type structure is a metastable phase, it is necessary to first synthesize a Na compound having a similar P2 type structure, and then ion-exchange at least a part of the Na of the Na compound with Li to obtain the O2 type structure. Therefore, in the manufacturing method of the present disclosure, a Na compound having a P2 type structure is first obtained. The Na compound having a P2 type structure can be synthesized by a known method. For example, a mixture is obtained by mixing an ion source capable of forming a precipitate in an aqueous solution with a transition metal ion, a transition metal source, a precipitate derived from the transition metal source, and a Na source, and the mixture is optionally molded and pre-fired, and then the mixture is fired, whereby a Na compound having a P2 type structure can be synthesized.

[0046] Examples of the ion source capable of forming a precipitate with the transition metal ion include salts such as carbonates and nitrates, sodium hydroxide, and sodium oxide. Examples of the transition metal source include salts such as nitrates, sulfates, and carbonates, and hydroxides. The ion source and the transition metal source may be prepared as solutions, and then the solutions may be dropped and mixed to obtain a precipitate. In this case, various sodium compounds may be used as bases, and an aqueous ammonia solution may be added to adjust the basicity. The amount of the Na source mixed before the precipitate is calcined may be determined taking into account the amount of Na lost during the calcination. The preliminary calcination is performed at a temperature equal to or lower than the main calcination. The preliminary calcination may be omitted. The main calcination may be performed at a temperature of, for example, 700°C or higher and 1100°C or lower. The temperature is preferably 800°C or higher and 1000°C or lower. If the calcination temperature is too low, Na doping is not performed, and if the calcination temperature is too high, an O3 type structure is likely to be formed instead of a P2 type structure. The firing atmosphere is not particularly limited, and may be, for example, an oxygen-containing atmosphere such as air atmosphere, or an inert gas atmosphere.

[0047] 4.2 Ion exchange In the manufacturing method of the present disclosure, at least a part of Na in the above Na compound is replaced with Li by ion exchange using lithium halide to obtain a Li compound having an O2 type structure. There are two types of ion exchange: a method using an aqueous solution containing lithium halide and a method using a molten salt of lithium halide and other lithium salts. In either case, since lithium halide is used, a reaction phase containing halogen may be formed on the surface of the Li compound after ion exchange. From the viewpoint that the P2 type structure is easily broken by the intrusion of water and from the viewpoint of crystallinity, the method using the molten salt is preferable among the above two methods. That is, by mixing the above Na compound having the P2 type structure with the molten salt and heating it to a temperature equal to or higher than the melting point of the molten salt, at least a part of Na in the Na compound can be replaced with Li by ion exchange.

[0048] The lithium halide constituting the molten salt is preferably at least one of lithium chloride, lithium bromide, and lithium iodide. The other lithium salt constituting the molten salt is preferably lithium nitrate. By using the molten salt, the melting point becomes lower than when the lithium halide or other lithium salt is used alone, and ion exchange can be performed at a lower temperature. In the molten salt, the mixture ratio of the lithium halide and other lithium salt is not particularly limited.

[0049] The temperature in the ion exchange may be, for example, 600°C or less, 500°C or less, 400°C or less, or 350°C or less, and may be room temperature or more or 100°C or more. If the temperature in the ion exchange is too high, the stable phase O3 type structure is likely to be generated instead of the O2 type structure. When an aqueous solution containing lithium halide is used, the ion exchange is possible even at room temperature. On the other hand, when a molten salt is used, the ion exchange is performed at a temperature equal to or higher than the melting point of the molten salt, as described above. From the viewpoint of shortening the time required for the ion exchange, the temperature in the ion exchange may be 100°C or more.

[0050] 4.3 Reduction of halogens on surfaces As described above, in the manufacturing method of the present disclosure, a reaction phase with lithium halide is formed on the surface of the Li compound obtained after ion exchange, and the reaction phase is likely to hinder the diffusion of lithium ions. In order to solve this problem, in the manufacturing method of the present disclosure, the amount of halogen present per unit area on the surface of the Li compound is reduced. Specifically, the reaction phase is removed from the surface of the Li compound, or the Li compound is crushed to expose a new surface, thereby relatively reducing the proportion of halogen present on the entire surface of the Li compound. More specifically, for example, the amount of halogen present per unit area on the surface of the Li compound can be reduced by at least one of pickling the surface of the Li compound and crushing the primary particles of the Li compound by mechanical milling.

[0051] The pickling conditions are not particularly limited, and any conditions are acceptable as long as the surface of the Li compound can be cleaned and the amount of halogen can be reduced. There is also no particular limit to the type of acid used in the pickling. For example, the surface of the Li compound can be cleaned with hydrochloric acid. There is also no particular limit to the pickling temperature or time.

[0052] When the primary particles of the Li compound are crushed by mechanical milling, the specific conditions are not particularly limited. However, in mechanical milling for simply mixing powders, although it is possible to eliminate particle aggregation (disintegrate secondary particles), it is practically impossible to crush the primary particles, and it is difficult to reduce the amount of halogen present per unit area on the surface of the Li compound. In order to crush the primary particles of the Li compound to obtain a new surface, it is necessary to impart high energy to the Li compound in mechanical milling. In this regard, in the manufacturing method disclosed herein, it is necessary to adopt mechanical milling with large collision energy, which is different from mechanical milling for simply mixing powders, etc. For example, when a planetary ball mill is adopted, it is considered possible to crush the primary particles of the Li compound by setting the rotation speed at a high speed (for example, 100 rpm or more) and the rotation time at a long time. In addition to the planetary ball mill, mechanical milling with high collision energy such as a vibration ball mill, an attritor ball mill, a bead mill, and a uniaxial rotating ball mill with an inner diameter of 30 cm or more may be adopted. EXAMPLES

[0053] The technology of the present disclosure will be described in more detail below with reference to examples, but the technology of the present disclosure is not limited to the following examples.

[0054] 1. Example 1 1.1 Synthesis of sodium compounds with P2 structure Mn(NO3)2·6H2O, Ni(NO3)2·6H2O, and Co(NO3)2·6H2O were used as raw materials and dissolved in pure water so that the molar ratio of Mn, Ni, and Co was 5:2:3. Meanwhile, a Na2CO3 solution with a concentration of 12 wt% was prepared, and these two solutions were simultaneously dropped into a beaker. At this time, the titration speed was controlled so that the pH was 7.0 or more and less than 7.1. After the titration was completed, the mixed solution was stirred at 50°C and 300 rpm for 24 hours. The obtained reaction product was washed with pure water, and only the precipitated powder was separated by centrifugation. The obtained powder was dried at 120°C for 48 hours and then crushed in an agate mortar to obtain a powder. Na2CO3 was added to the obtained powder, and ... 0.75 Mn 0.5 Ni 0.2 Co 0.3 The mixture was mixed to obtain O2. The mixed powder was pressed under a load of 2 tons using cold isostatic pressing to produce pellets. The pellets obtained were pre-fired at 600°C for 6 hours in an air atmosphere, and then fired at 900°C for 24 hours to synthesize a Na compound with a P2 type structure.

[0055] 1.2 Ion exchange LiNO3 and LiCl were mixed in a mass ratio of 88:12, and weighed out so that the molar ratio of Li was 10 times that of the Na compound with a P2 type structure. The Na compound was mixed with the LiNO3·LiCl mixed powder, and ion exchange was carried out at 280°C for 1 hour in an air atmosphere. After the ion exchange, water was added to dissolve the excess salt, and the mixture was washed with water to obtain a Li compound with an O2 type structure.

[0056] 1.3 Reduction of halogens on surfaces The Li compound having an O2 structure was mixed with 50 times the mass of zirconia balls (φ5 mm), placed in a pot, and crushed at 400 rpm for 1 hour using a planetary ball mill. After the crushing process, the positive electrode active material for evaluation was collected using a stainless steel sieve.

[0057] 1.4 Preparation of the positive electrode 85 g of the positive electrode active material (powder after planetary ball milling) obtained as described above and 10 g of carbon black as a conductive additive were uniformly kneaded in 125 mL of n-methylpyrrolidone solution in which 5 g of PVdF was dissolved as a binder, to prepare a positive electrode composite paste. This paste was applied to an Al current collector with a thickness of 15 μm in a weight ratio of 6 mg / cm. 2 The laminate was then pressed to a paste thickness of 45 μm and a paste density of 2.4 g / cm. 3 Finally, this laminate was cut to a diameter of 16 mm to obtain a positive electrode.

[0058] 1.5 Preparation of the negative electrode The Li foil was cut to a diameter of 19 mm to obtain a negative electrode.

[0059] 1.6 Preparation of lithium-ion secondary battery A CR2032 coin cell was fabricated using the obtained positive and negative electrodes. A PP porous separator was used as the separator, and the electrolyte was a mixture of EC (ethylene carbonate) and DMC (dimethyl carbonate) in a volume ratio of 3:7, with lithium hexafluorophosphate (LiPF6) dissolved at a concentration of 1 mol / L as the supporting electrolyte.

[0060] 2. Example 2 A Li compound having an O2 type structure was obtained in the same manner as in Example 1. The obtained Li compound was crushed by a uniaxial rotating ball mill using a resin pot with a diameter of 7 cm and zirconia balls with a diameter of 5 mm instead of crushing by a planetary ball mill, and the crushed powder was pickled with dilute hydrochloric acid to obtain a positive electrode active material. A lithium ion secondary battery was obtained using the positive electrode active material in the same manner as in Example 1.

[0061] 3. Comparative Example 1 A Li compound having an O2 type structure was obtained in the same manner as in Example 1. The obtained Li compound was crushed by a uniaxial rotating ball mill using a resin pot with a diameter of 7 cm and a zirconia ball with a diameter of 5 mm instead of crushing by a planetary ball mill, and the powder after crushing was used as it is as a positive electrode active material without being washed with an acid. A lithium ion secondary battery was obtained by using the positive electrode active material in the same manner as in Example 1.

[0062] 4. Evaluation 4.1 Identification of crystalline phases by XRD The crystal phase of each of the positive electrode active materials obtained in Examples 1 and 2 and Comparative Example 1 was identified by powder X-ray diffraction. The results are shown in Figure 2. As shown in Figure 2, each of the positive electrode active materials had an O2 type structure (and its derived structure).

[0063] 4.2 Identification of composition by ICP-AES ICP-AES measurements were performed on each of the positive electrode active materials obtained in Examples 1 and 2 and Comparative Example 1. The results are shown in Table 1 below. The compositions shown in Table 1 below are standardized so that the sum of the transition metal compositions is 1.00. As shown in Table 1, it can be seen that the target compositions were obtained for each positive electrode active material.

[0064] [Table 1]

[0065] 4.3 Analysis by XPS The surfaces of the positive electrode active materials obtained in Examples 1 and 2 and Comparative Example 1 were analyzed by XPS. FIG. 3 shows the XPS spectrum at around 200 eV. In addition, the following Table 2 shows the value of the ratio I1 / I2 of the peak intensity I1 derived from the 2p electrons of Cl and the peak intensity I2 derived from the 1s electrons of oxygen for each positive electrode active material. As shown in FIG. 3, for the positive electrode active materials according to Examples 1 and 2, the peak derived from the 2p electrons of Cl is not clearly confirmed, and it can be determined that Cl is not substantially present on the surface of the positive electrode active material. In contrast, for the positive electrode active material according to Comparative Example 1, the peak derived from the 2p electrons of Cl is clearly confirmed, and it can be determined that Cl is present on the surface of the positive electrode active material. As shown in the following Table 2, for the positive electrode active materials according to Examples 1 and 2, the ratio I1 / I2 was 1 / 1000 or less, whereas for the positive electrode active material according to Comparative Example 1, the ratio I1 / I2 was more than 1 / 1000.

[0066] [Table 2]

[0067] 4.4 Evaluation of charge / discharge capacity Charge and discharge tests were performed at rates of 0.1C, 0.5C, 1C, and 5C for each of the lithium ion secondary batteries produced in Examples 1 and 2 and Comparative Example 1, and the charge and discharge capacities at each rate were measured. In the charge and discharge tests, charging was performed up to 4.8V, and discharging was performed up to 2.0V. The results are shown in Table 3 below. As shown in Table 3 below, the lithium ion secondary batteries according to Examples 1 and 2 can ensure high charge and discharge capacities during high-speed charging and discharging, compared to the lithium ion secondary battery according to Comparative Example 1. Specifically, it can be seen that in Examples 1 and 2, the charge and discharge capacity at 5C is 60% or more of the charge and discharge capacity at 0.1C, whereas in Comparative Example 1, it is significantly reduced to about 30%.

[0068] [Table 3]

[0069] The reason why the capacity at the time of high-speed charge and discharge in Comparative Example 1 is greatly decreased is considered to be as follows. That is, as shown in Table 2 above, in Comparative Example 1, a large amount of Cl exists on the surface of the positive electrode active material. This is due to lithium chloride during ion exchange, and it is recognized that a reaction phase containing Cl was formed on the surface of the Li compound after ion exchange. It is considered that this reaction phase inhibits the diffusion of lithium ions. That is, in Comparative Example 1, the presence of the reaction phase slows down the diffusion of lithium ions on the surface of the positive electrode active material, and lithium ions cannot be sufficiently inserted and removed from the positive electrode active material during high-speed charge and discharge, and the charge and discharge capacity is greatly decreased. In contrast, the reaction phase containing Cl is substantially absent (even if it exists, it is very small) on the surface of the positive electrode active material according to Examples 1 and 2, so it is considered that lithium ions can be sufficiently inserted and removed from the positive electrode active material during high-speed charge and discharge, and high charge and discharge capacity can be ensured.

[0070] 5. Supplementary Information In the above, the case where lithium chloride is used as the lithium halide used during ion exchange is exemplified, but the technology of the present disclosure is not limited to this form. Even when a lithium halide other than lithium chloride is used, the same problem as in Comparative Example 1 occurs, but the problem can be solved by reducing the amount of halogen present on the surface of the positive electrode active material as in Examples 1 and 2. In addition, in the above, a positive electrode active material having a predetermined composition is exemplified as having an O2 type structure, but the composition of the positive electrode active material is not limited to this as long as it can maintain the O2 type structure. In addition, even if the positive electrode active material contains doping elements such as B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo and W, the same effect can be achieved. [Explanation of symbols]

[0071] 10 positive electrode 11 Cathode active material layer 12 Positive electrode current collector 20 Electrolyte layer 30 Negative electrode 31 Negative active material layer 32 Negative electrode collector 100 Secondary batteries

Claims

1. A positive electrode active material having an O2 type structure, When the surface of the positive electrode active material is analyzed by X-ray photoelectron spectroscopy (XPS), a peak intensity I 1 and the peak intensity I due to the oxygen 1s electron 2 Comparison with I 1 / I 2 becomes 1 / 1000 or less. Cathode active material.

2. Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O 2 (wherein the relationships 0≦a≦1, 0≦b≦0.05, x+y+z=1, and 0≦p+q+r≦0.2 are satisfied, and M is at least one element selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W), The positive electrode active material according to claim 1 .

3. A lithium ion secondary battery having a positive electrode, an electrolyte layer, and a negative electrode, The positive electrode comprises the positive electrode active material according to claim 1 or 2. Lithium-ion secondary battery.

Citation Information

Patent Citations

  • Nonaqueous secondary battery, positive electrode, and manufacturing method thereof

    JP2008084652A

  • Method for producing positive electrode active material and method for manufacturing lithium ion battery

    JP2021068555A

  • Method for producing positive electrode active material and method for manufacturing lithium ion battery

    JP2021068556A

  • Positive electrode active material for non-aqueous electrolyte secondary cell, and non-aqueous electrolyte secondary cell using same

    WO2014155988A1

  • Positive electrode active material for nonaqueous electrolyte secondary batteries and method for producing same

    WO2015049796A1